Cell-tissue therapy of fetoplacental origin in recurrent implantation failure and chronic endometritis: a clinical case report - Konoplia, Lina; Feskova, Anna (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):235